2015
DOI: 10.1128/jvi.01527-15
|View full text |Cite
|
Sign up to set email alerts
|

The Breadth of Expandable Memory CD8 + T Cells Inversely Correlates with Residual Viral Loads in HIV Elite Controllers

Abstract: Previous studies have shown that elite controllers with minimal effector T cell responses harbor a low-frequency, readily expandable, highly functional, and broadly directed memory population. Here, we interrogated the in vivo relevance of this cell population by investigating whether the breadth of expandable memory responses is associated with the magnitude of residual viremia in individuals achieving durable suppression of HIV infection. HIV-specific memory CD8؉ T cells were expanded by using autologous epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 78 publications
(89 reference statements)
0
37
0
Order By: Relevance
“…However, we have previously shown that suppressive CD8 T cell activity in HIV-1 controllers remained low in some donors even when autologous virus was used (39). Alternatively, the absence of suppressive activity may be a consequence of the stringent control of viremia, resulting in the contraction of the HIV-2-specific CD8 + T cell response to a small pool of high-quality memory cells that fall below the detection threshold of our assay (49,52,53). Moreover, we were only able to analyze the CD8 + T cell response in blood and would not be able to measure more robust responses that were active locally in patient tissues (54).…”
Section: Discussionmentioning
confidence: 87%
“…However, we have previously shown that suppressive CD8 T cell activity in HIV-1 controllers remained low in some donors even when autologous virus was used (39). Alternatively, the absence of suppressive activity may be a consequence of the stringent control of viremia, resulting in the contraction of the HIV-2-specific CD8 + T cell response to a small pool of high-quality memory cells that fall below the detection threshold of our assay (49,52,53). Moreover, we were only able to analyze the CD8 + T cell response in blood and would not be able to measure more robust responses that were active locally in patient tissues (54).…”
Section: Discussionmentioning
confidence: 87%
“…This broadening of T-cell responses may reflect processes similar to those seen in the immune response to infectious disease vaccinations (32)(33)(34). However, the specificity and type of T cells recruited to the prostate tissue remain unknown at this time.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may be particularly relevant and efficient in the long term in HICs, whose target cells are also strongly resistant to HIV-1 infection, particularly at low infectious doses (17,40), providing an additional barrier to viral amplification. In addition, weakly responsive memory CD8 ϩ T cells in HICs are ready to react and expand promptly in response to stochastic viral amplification events (12,50) (Fig. 5C), thereby ensuring natural control of HIV-1 infection in the very long term.…”
Section: Discussionmentioning
confidence: 99%